Global raptor research and conservation priorities: Tropical raptors fall prey to knowledge gaps. Issue 6 (21st February 2019) - Buechley, Evan R.; Santangeli, Andrea; Girardello, Marco; Neate‐Clegg, Montague H.C.; Oleyar, Dave; McClure, Christopher J.W.; Şekercioğlu, Çagan H.
Abstract: Aim: Raptors serve critical ecological functions, are particularly extinction‐prone and are often used as environmental indicators and flagship species. Yet, there is no global framework to prioritize research and conservation actions on them. We identify for the first time the factors driving extinction risk and scientific attention on raptors and develop a novel research and conservation priority index (RCPI) to identify global research and conservation priorities. Location: Global. Methods: We use random forest models based on ecological traits and extrinsic data to identify the drivers of risk and scientific attention in all raptors. We then map global research and conservation priorities. Lastly, we model where priorities fall relative to country‐level human social indicators. Results: Raptors with small geographic ranges, scavengers, forest‐dependent species and those with slow life histories are particularly extinction‐prone. Research is extremely biased towards a small fraction of raptor species: 10 species (1.8% of all raptors) account for one‐third of all research, while one‐fifth of species have no publications. Species with small geographic ranges and those inhabiting less developed countries are greatly understudied. Regions of Latin America, Africa and Southeast Asia are identified as particularly high priority for raptor research and conservation. These priorities are highly concentrated in developing countries, indicating a global mismatch between priorities and capacity for research and conservation. Main conclusions: A redistribution of scientific attention and conservation efforts towards developing tropical countries and the least‐studied, extinction‐prone species is critical to conserve raptors and their ecological functions worldwide. We identify clear taxonomic and geographic research and conservation priorities for all raptors, and our methodology can be applied across other taxa to prioritize scientific investment.